Mapping Two Decades of Research on Faded Examples and Science Reasoning: Bibliometric Analysis Using VOSviewer - Taufiq Fathurrozi; Muhammad Syaipul Hayat; Joko Siswanto (Jurnal Penelitian Pembelajaran Fisika, 2025)
Scientific reasoning skills are key competencies in 21st-century science education. One learning strategy believed to promote the development of these skills is the faded example, which involves presenting examples whose solutions are gradually reduced to support students' independent thinking processes. This study aims to map trends and relationships between the faded example strategy and scientific reasoning through bibliometric analysis using VOSviewer. A total of 87 articles meeting the inclusion criteria were analyzed thematically. The visualization results show that the topic of faded examples is frequently associated with problem-solving, while scientific reasoning appears more often in the broader context of science education. Although no explicit relationship has been found in the existing literature, there are indications of a conceptual connection between the two. Furthermore, further research is needed that explicitly and systematically integrates the faded example strategy into the development of scientific reasoning in inquiry-based science learning.